EXAMINING THE IMPACT OF TANGIBLE RESOURCES, KNOWLEDGE MANAGEMENT AND HUMAN RESOURCES COMPETENCE ON EMPLOYEE PERFORMANCE - Andrie Kurniawan; Faroman Syarief; Fahmi Kamal; Bryan Givan (Jurnal Ekonomi, 2023)
This study aims to investigate the effect of Tangible Resources, Knowledge Management, and Human Resources Competence on employee performance in the banking industry. The research method used is a quantitative method using multiple linear regression to analyze the data. The research sample consisted of 69 employees of BUMN Banks in Jakarta. the research results show that Tangible Resources and Knowledge Management have a significant influence on employee performance. Knowledge Management also has a significant influence on employee performance. However, the research results show that Human Resources Competence has no significant effect on employee performance. The research findings provide practical implications for the management of banking organizations in managing their resources. Appropriate investment in Tangible Resources and effective management of knowledge through Knowledge Management can improve employee performance. In addition, it is important for organizations to pay attention to and develop individual employee competencies in the context of Human Resources Competence.